PENGEMBANGAN BOOKLET BERBANTU MEDIA ULAR TANGGA PADA MATERI KOLOID UNTUK SISWA KELAS XI IPA SMA/MA SEDERAJAT - Windri Anita; Dwi Putri Musdansi; Rosa Murwindra (Universitas Islam Kuantan Singingi, 2023)
This research on booklet development assisted by snakes and ladders media aims to explain the feasibility of developing a booklet assisted by snakes and ladders media in the colloid system subject for class XI SMA/MA equivalent students. This research method is research and development (R&D) with a 4D development model which includes the Define, Design, Develop, and Disseminate stages. The data collection instruments used were through material expert validation sheets, learning media validation sheets, and student response validation sheets. The data analysis technique used is by calculating the percentage score of expert judgment. The results showed that the developed snake and ladder assisted Booklet media met the fairly valid category of three material experts, which was 76,78%, met the valid category of three media experts by 81,01%, and fulfill the valid category of student responses by 90%.